PEMANFAATAN LIMBAH TAHU SEBAGAI POTENSI SUMBER BELAJAR IPA PADA MATERI PENGELOLAAN LINGKUNGAN - Haning Hasbiyati (JURNAL BIOSHELL, 2015)
To achieve the goal of learning science, the science teacher demanded more creative, initiatives, and innovative in finding the source of learning for the learners. Environment around us can be an attractive alternative learning resources. In the environmental management materials science subjects junior class VII, one of the local potential that can be raised as a source of student learning is waste processing know.The aim of research to determine whether the use of waste as a source of know can potentially learn science in environmental management material. This study is exploratory research. Data analysis techniques in this study using qualitative descriptive analysis techniques. Research activities include collecting data, analyzing the data, the data meginterprestasi, and ends with a conclusion that refers to analyzing the data with the analysis of the suitability of the terms of learning resources.Results of this study indicate that the use of waste as a source of know can potentially learn science in environmental management material in the form of process and product research. The process of observation in the form of scientific work of making out and identification of waste, while the utilization of waste products in the form know that the manufacture of food products nuggets of tofu and Nata de Soya from wastewater out an effort to address environmental pollution.Keywords: waste , learning resources , environment, and science